2021
DOI: 10.3389/fevo.2021.660207
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Phenotypes of Sterile Hybrid Males From Reciprocal Crosses Between Species of the Anopheles gambiae Complex

Abstract: Haldane’s rule of speciation states that sterility or inviability affects the heterogametic sex of inter-species hybrids. Darwin’s corollary to Haldane’s rule implies that there are asymmetric phenotypes in inter-species hybrids from reciprocal crosses. Studying the phenotypes of F1 hybrids among closely related species of malaria mosquitoes can assist researchers in identifying the genetic factors and molecular mechanisms of speciation. To characterize phenotypes of sterile hybrid males in the Anopheles gambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…MAG proteins are an essential component of seminal fluid deposited into the An. gambiae female reproductive tract during copulation and they play important roles in inducing female post-mating responses, including oviposition and monogamy [ 80 , 81 , 82 , 83 ]. An over-representation of MAG-biased genes on the X chromosome [ 26 ] suggests that components of male reproductive biology in malaria mosquitoes can be antagonistic.…”
Section: Discussionmentioning
confidence: 99%
“…MAG proteins are an essential component of seminal fluid deposited into the An. gambiae female reproductive tract during copulation and they play important roles in inducing female post-mating responses, including oviposition and monogamy [ 80 , 81 , 82 , 83 ]. An over-representation of MAG-biased genes on the X chromosome [ 26 ] suggests that components of male reproductive biology in malaria mosquitoes can be antagonistic.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae species complex contains the most important malaria vectors in sub-Saharan Africa ( O’Loughlin, 2020 ). Although some studies have shown that lab colonies of different species can cross-mate and produce viable eggs ( Liang et al, 2021 ), five species do not overlap geographically, whilst there are pre-mating barriers between other species ( Diabaté et al, 2009 ). Notably though, hybridisation has been observed between wild An.…”
Section: Endogenous Gene Targets For More Efficient Crispr-based Homi...mentioning
confidence: 99%